The SPIRAL1 charge breeder: key points for a high-performance 1+ beam injection. (12th May 2021) - Maunoury, L.; Kamalou, O.; Cam, J.F.; Damoy, S.; Delahaye, P.; Dubois, M.; Frigot, R.; Hormigos, S.; Vandamme, C.
Abstract: The SPIRAL1 charge breeder is now under operation. Radioactive beam has already been delivered [1] to physicists for performing experiments. Although charge breeding efficiencies demonstrated high performances for stable ion beams, efficiencies regarding radioactive ion beams were found to be lower than expected in the first experiment. The beam optics, prior to the injection of the 1+ ions into the SPIRAL1 charge breeder, is of prime importance [2] for reaching such high efficiencies. Moreover, the intensities of the radioactive ion beams are so low that it is very difficult to tune the charge breeder. The tuning of the charge breeder for radioactive ion beams requires a particular procedure often referred to as "blind tuning". A stable beam with a similar Brho (within a few percent) is required to find the set of optic parameters before tuning the radioactive ion beam. Hence, it has been decided to focus our efforts on this procedure in order to get control of the 1+ beam optics leading to high charge breeding efficiencies whatever the 1+ mass, energy and Target Ion Source System (TISS) used. Knowing that each TISS provides ion beams with a specific energy spread ΔE, and given that the energy acceptance window of the charge breeder is rather narrow, this parameter must also play an important role in determining the overall charge breeding efficiency. This contribution will show the strategy undertaken to overcome the difficulties encountered in the charge breeding tuning with 1+ radioactive ion beams from the different ion sources, and the results already obtained. A series of experiments have been done to record beam parameters as well as beam profiles in two modes: "shooting through" and 1+/N+. Simulations have been developed to replicate the measurements: for this purpose a combination of SIMION and TraceWin software was used. The final goal is to define a set of beam optics reliable enough for operation covering a large range of 1+ mass, energy and emittance; applying the resulting set of parameters must eventually allow to approach the expected optimal charge breeder performances while producing a radioactive ion beam.